Blood lactate and heart rate during national and international women's basketball - Rodriguez-Alonso, M.; Fernandez-Garcia, B.; Perez-Landaluce, J. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: In order to measure game intensity in female basketball players, 2 teams (Olympic National Team - I -and a team at 1st National Division - N) were studied for a total of 12 games (10 official competitions and 2 practice games -P). Methods: Both blood lactate concentration ([La]b) and mean heart rate (HR) were measured during the games and then compared with a progressive field test where maximal blood lactate (max[La]b), individual lactate threshold and maximal heart rate (HR max) values were obtained. All different categories (International, National and Practice) and positions (Guard, Forward and Center) were taken into account in this study. Results: Differences (p<0.05) in HR were found between all positions (Guard=185±5.9; Forward=175±11 and Center=167±12 beats x min-1) and between the International team and the rest of the categories (International=186±6; National=175±13 and Practice=170±11 beats x min-1). The [La]b differed between the Guard and the other 2 positions (Guard=5.7±2.1; Forward=4.2±2.1 and Center=3.9±2.0 mmol x L-1) and between Practice and the rest of the categories (International=5.0±2.3; National=5.2±2.0 and Practice=2.7±1.2 mmol x x L-1). The game intensity of International players reached 94.6% of their maximum HR value, whereas National players reached 90.8%, this percentage descending to 89.8% during Practice. International games reached the individual lactate threshold at 89.2% of the maximum HR; National games at 88.6%. Conclusion: We can conclude that the game intensity of female basketball increases according to the level of competition. It may also differ according to playing position, being greatest in guards. The game intensity at international level surpasses the individual lactate threshold, whereas it reaches a lower level in training games.